Formulation and Evaluation of Starch Phosphate-Based Cream Derived from Manihot esculentus - Achor, Mohammed; Abdullahi, Buhari Muntaqa (Pharmaceutical Fronts, 2023)
Starch is an important excipient employed in the pharmaceutical industry but irrespective of its source, the native starch is undesirable for many applications because of its inability to withstand processing conditions and hence needs its modification to achieve the desired properties. This study aimed to synthesize starch phosphate through the modification of starch obtained from Manihot esculentus, and then explore its potential in the preparation of cream formulations. In the present study, the starch was extracted from M. esculentus (cassava), then phosphorylated by reacting with varied concentrations of disodium hydrogen phosphate, anhydrous (Na2HPO4, 0.05, 0.1, and 0.2 mol/dm3) under pH 6. A standard wet chemistry method was used for the determination of the degree of substitution by phosphate (DSp) of modified starch, and Fourier transform infrared (FTIR) spectra were used for structure identification. The starch phosphate obtained was employed to develop a cream formulation. The physicochemical properties of the formulation were further evaluated. Calamine cream BP was utilized as a control. Our result indicated that a higher concentration of Na2HPO4 favors a higher DSp (0.047). FTIR spectra of the modified starch suggested a new peak at 1,090 cm−1 (P-OR). The cream formulated with a high DSp of starch phosphate demonstrated good physicochemical properties with spreadability (7.84–8.65 gcm/s), pH (6.5–7.0), viscosity (267–296 cp), extrudability (2.05–2.62%) and physical stability, and were smooth, opaque, greasy, homogeneous, and easily removed on washing with water. Statistical analysis showed that there was no significant difference between the starch phosphate-based cream and the control, but a significant difference between the starch phosphate-based cream and a native starch-based cream. Given the above, starch phosphate with a high DSp can be prepared from M. esculentus starch and utilized as a promising emulsifying agent in cream formulation due to its being more widely available, more stable, and cost-effective.
Keywords: Manihot esculentus; starch phosphate; cream; disodium hydrogen phosphate